2016
DOI: 10.1111/pai.12529
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological characteristics of a pediatric population with food protein‐induced enterocolitis syndrome (FPIES) to fish

Abstract: FPIES caused by fish in many cases presents with severe clinical manifestations. Patch test has poor diagnostic value, and OFC is the gold standard to test tolerance. The cytokine TNF-α may be implicated in the clinical symptoms. Higher expression of HLA-DR in dendritic cells has also been detected in our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 29 publications
2
56
0
4
Order By: Relevance
“…Miceli et al in the past had suggested that FPIES as a diagnosis should be considered until at least 2 years of age. However, it is already recognized in the International Consensus Guidelines of FPIES that this diagnosis can occur later in childhood and that egg, fish and shellfish FPIES has been described in a small adult case series . There are significant limitations in regard to the published data on age of onset in FPIES due to it still being a poorly recognized disorder.…”
Section: The Natural Course Of Non‐ige‐mediated Gastrointestinal Allementioning
confidence: 99%
See 2 more Smart Citations
“…Miceli et al in the past had suggested that FPIES as a diagnosis should be considered until at least 2 years of age. However, it is already recognized in the International Consensus Guidelines of FPIES that this diagnosis can occur later in childhood and that egg, fish and shellfish FPIES has been described in a small adult case series . There are significant limitations in regard to the published data on age of onset in FPIES due to it still being a poorly recognized disorder.…”
Section: The Natural Course Of Non‐ige‐mediated Gastrointestinal Allementioning
confidence: 99%
“…However, it is already recognized in the International Consensus Guidelines of FPIES that this diagnosis can occur later in childhood and that egg, fish and shellfish FPIES has been described in a small adult case series. 46,49,50 There are significant limitations in regard to the published data on age of onset in FPIES due to it still being a poorly recognized disorder. Ludman et al 44 found that patients with FPIES in the United Kingdom had a mean symptom duration for 20.2 months, before a referral to a specialist allergy centre was made.…”
Section: Food Protein-induced Enterocolitis Syndrome (Fpies)mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the solid foods, rice is considered one of the most common causative foods worldwide [1], but it varies depending on the geographic area. In the Mediterranean countries, such as Spain or Italy, fish is the most important solid food trigger of FPIES [2-5]. …”
Section: Introductionmentioning
confidence: 99%
“…FPIES caused by finned fish (eg, codfish, salmon, tuna) has been described as one of the most common triggers in infants and toddlers in Spain and Italy, likely reflecting the importance of fish in the diet and the relatively earlier age of introduction compared with other countries [14][15][16][39][40][41][42][43][44]. Table 2 presents the characteristics of fish-induced FPIES.…”
Section: Fpies Caused By Fishmentioning
confidence: 99%